Accidental discovery of cholecystoduodenal fistula during laparoscopic cholecystectomy: a case report - Huang, Rui; Tian, Jian-Xing; Deng, Xu; Zhu, Zong-Long; Tian, Wei; Yang, Chun-Yuan; Xia, Ming; Pan, Wei (Frontiers in Surgery, 2025)
Cholecystoduodenal fistula (CDF) is a rare complication of cholelithiasis. Sometimes, a preoperative examination does not fully detect CDF and may have an impact on the conduct of the surgery. Sometimes, clinicians fail to accurately determine the presence of CDF, which may have an impact on the conduct of the procedure. Here, we report the diagnosis and management of a patient with a CDF that was accidentally detected intraoperatively. The patient was hospitalized twice in our hospital due to excessive inflammation around the gallbladder and combined with choledochal stones. During the second hospitalization, a CDF was accidentally found during laparoscopic cholecystectomy. We repaired the fistula, ligated the cystic duct, and removed the gallbladder laparoscopically while ensuring patient safety. In the absence of preoperative detection of a cholecystoenteric fistula (CEF), intraoperative judgment and postoperative management are of particular importance, which is what will be discussed in this article.